Future of Radio Broadcasting and Audience Behavior in Streaming and Apps - Muslikhin, Muslikhin (Jurnal Pustaka Komunikasi, 2025)
This descriptive research aims to understand listener behavior in consuming live streaming and radio broadcast applications in Indonesia to support the sustainability of radio broadcasting businesses.  The study employs a quantitative method with data collection techniques through a survey distributed via Google Forms.  The survey was conducted from August 1, 2024, to October 17, 2024.  The population of this study consists of individuals who actively access radio through digital platforms, either through live streaming or mobile radio broadcast applications.  The sampling technique used is convenience sampling, with inclusion criteria: aged at least 16 years, having internet access, and having listened to digital radio in the last six months.  The number of respondents was 223 individuals, determined based on the Lemeshow formula with a confidence level of 95% and a margin of error of 0.066.  Data were analyzed using descriptive statistics.  The research results show that the majority of streaming radio listeners are Generation Z (54.5%) and millennials (25%), with a female majority (60.3%).  50.2% of listeners access digital radio through mobile applications while traveling.  The reason the audience consumes streaming radio is due to better quality (43.8%), easier accessibility (60.6%), and wide reach as long as there is an internet connection (63.1%).  These findings have implications for radio station managers to enhance their digital strategies to ensure their business remains sustainable amidst changing listener behavior and increasingly fierce media industry competition.